PERKEMBANGAN KARAKTER HADES DALAM NOVEL HAVE A HOT TIME, HADES! KARYA KATE MCMULLAN (ANALISIS PSIKOLOGI) - JASTIN, CRISANDI (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2017)
ABSTRACT Â Â ThisÂ  researchÂ  isÂ  entitledÂ  â€œPerkembanganÂ  KarakterÂ  HadesÂ  DalamÂ  NovelÂ  Have aÂ  HotÂ  Time,Â  Hades!Â  KaryaÂ  KateÂ  McMullanÂ  (AnalisisÂ  Psikologi)â€.Â  TheÂ  aimsÂ  ofÂ  thisÂ  researchÂ  isÂ  toÂ  identifyÂ  andÂ  analyzeÂ  theÂ  stagesÂ  ofÂ  characterÂ  developmentÂ  ofÂ  HadesÂ  fromÂ  psychologicalÂ  perspective,Â  asÂ  wellÂ  asÂ  toÂ  analyzeÂ  theÂ  characterÂ  ofÂ  HadesÂ  himself. Â InÂ  termsÂ  ofÂ  methodology,Â  theÂ  theoryÂ  usedÂ  forÂ  thisÂ  analysisÂ  isÂ  the psychosocialÂ  developmentÂ  theoryÂ  byÂ  ErikÂ  EriksonÂ  inÂ  ChildhoodÂ  andÂ  Society (1950).Â  ThisÂ  researchÂ  alsoÂ  appliedÂ  theÂ  combinationÂ  ofÂ  twoÂ  approachesÂ  namelyÂ  theÂ  intrinsicÂ  andÂ  extrinsicÂ  approaches. Â TheÂ  resultÂ  ofÂ  thisÂ  researchÂ  showsÂ  thatÂ  HadesÂ  inÂ  theÂ  novelÂ  Have aÂ  HotÂ  Time,Â  Hades!Â Â  haveÂ  aÂ  uniqueÂ  andÂ  differentÂ  personalityÂ  thanÂ  theÂ  HadesÂ  generallyÂ  knownÂ  fromÂ  otherÂ  literaryÂ  works. TheyÂ  are,Â  critics,Â  sarcastic,Â  criticalÂ  thinking,Â  positiveÂ  thinking,Â  andÂ  compassionate.Â  WhileÂ  theÂ  stagesÂ  ofÂ  psychosocialÂ  developmentÂ  ofÂ  HadesÂ  thatÂ  areÂ  presentÂ  inÂ  theÂ  novelÂ  areÂ  Trust vs. Mistrust,Â  Autonomy vs. Shame and Doubt,Â  Initiative vs. Guilt,Â  Industry vs. Inferiority,Â  Identity vs. Confusion, Intimacy vs. Isolation,Â  andÂ  showsÂ  theÂ  resultÂ  ofÂ  HadesÂ  passÂ  allÂ  theÂ  stagesÂ  presentÂ  withÂ  theÂ  dominationÂ  ofÂ  positiveÂ  outcome.Â Â  Â Â ___________________________________________________________ Keywords:Â  characterÂ  development,Â  psychologicalÂ  analysis,Â  Hades